Vapor-deposited zeolitic imidazolate frameworks as gap-filling ultra-low-k dielectrics - Mikhail Krishtab (Nature Portfolio, 2019)
Insulating materials combining a high mechanical stability, a low dielectric constant and the ability to completely fill narrow gaps are essential to fabricate interconnects for future high-performance chips. Here, the authors integrate zeolitic imidazolate frameworks as ultra-low-k dielectrics within a 90 nm pitch metallization layer via selective vapor-based conversion of metal oxide films.